Work Stress, Work-Family Conflict, and Organizational Factors Related to Burnout: Stres Kerja, Konflik Kerja-Keluarga, dan Faktor Organisasi yang Berkaitan dengan Kelelahan Kerja - Iswahyuni, Lujeng; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Employee burnout has become a major concern in modern organizations due to increased job demands and work-life imbalance. Specific Background: PT. Welirang Tirta Mandiri faces productivity challenges caused by stress and limited organizational support. Gap: Previous studies have often examined stress or work-family conflict separately, while few analyzed these factors together with organizational climate and support. Aim: This study investigates the relationship among work stress, work-family conflict, organizational climate, and organizational support toward employee burnout. Results: Using quantitative methods and multiple linear regression, findings show that work stress, work-family conflict, and organizational climate positively affect burnout, while organizational support negatively correlates with burnout. Novelty: The simultaneous examination of psychological and organizational factors provides a holistic view of burnout predictors. Implications: The results emphasize the importance of strengthening organizational support to reduce employee burnout. Highlights:• Work stress and family conflict increase employee burnout• Organizational support reduces burnout level• Organizational climate significantly relates to burnout Keywords: Burnout, Work Stress, Organizational Climate, Work-Family Conflict, Organizational Support